Government Agricultural Intervention and Farm Household Income - Zednita Azriani; Hasnah Hasnah; Rika Hariance; Nuraini Budi Astuti; Syahdina Sarah (CV. Sakura Digital Nusantara, 2026)
Purpose – This study examines the effect of government agricultural intervention on farm household income and production across major agricultural subsectors. Design/methodology/approach - A quantitative approach was employed using data from 247 farmers who received government assistance across seven agricultural commodity-producing districts and cities. The analysis combines descriptive statistics and t-tests to assess changes in production and household income following intervention. Findings/Results - Government intervention increased agricultural production by approximately 7% overall. The largest increase occurred in the food crop subsector at 10%, followed by plantations at 8%, while the lowest increase was 4%. The t-test results confirm that government intervention significantly improves farm household income, with the strongest income response observed among food crop farmers. Originality/Value - This study demonstrates that government agricultural intervention can improve both production and household income, although its effectiveness varies across subsectors. The findings highlight the importance of combining production support with farm diversification and downstream processing to strengthen the sustainability of rural household income.